Ethnophysics Study of Reog Ponorogo Art in Physics Learning: A Study of Students' Interests and Understanding - Habibi*, Rohmad; Suprapto, Nadi; Prahani, Binar Kurnia; Satriawan, Muhammad; Nisa', Khoirun (Universitas Syiah Kuala, 2025)
Physics learning is still often considered abstract and less interesting by students, so a more contextual and relevant approach is needed. Ethnophysics, which connects the concepts of physics with the local culture, is one of the alternatives to increase students understanding and interest. This study aims to identify and analyze the influence of ethnophysics-based learning on studentslearning interests and assess its impact on students understanding of physics concepts. In this study used mixed method with concurrent triangulation approach, where quantitative data obtained through Likert scale questionnaire and compared with qualitative data from students open questions. The results showed that the integration of ethnophysics in physics learning has a positive impact, with an average score of students understanding of 3.65 (high category) and increased interest in learning with a score of 3.56 (high category). In addition, the effectiveness of culture-based learning was also rated high (3.65) by students. Concurrent triangulation approach shows most students can benefit cultural integration in physics learning. However, there are still some students who have difficulty in applying physics concepts to numerical problems. Therefore, this study recommends the use of problem based learning (PBL)model in ethnophysics-based LKPD as a strategy to strengthen students problem-solving skills. The conclusion obtained from this study is that the integration of ethnophysics in physics learning can improve students understanding, interest, and learning effectiveness. In addition, the development of culture-based learning with the PBL approach is recommended as an innovative strategy that not only enhances the understanding of physics but also preserves the local cultural heritage